Parties Matter: The Consequences of PRR Parties in Subnational Governments on Health Policy. Issue 4 (6th October 2022) - Falkenbach, Michelle
Abstract: Although the research surrounding PRR parties has increased over the years, health policies, an important part of the welfare system, have generally been neglected. Using an in-depth case-study approach, this article analyses the health policy consequences of PRR parties in Austrian and Italian subnational governments over time, thereby expanding the units of analysis while also looking at an understudied level of government. The findings indicate a propensity towards neoliberalism, combined with accents of welfare chauvinism in Austria and a strategy of shutting down the Freedom Party of Austria. In the case of Italy, both regional cases mark a desire for welfare chauvinism but an inability to restrict healthcare access directly. In all four cases (except Burgenland), the PRR parties are consistently chauvinistic (despite seeming to prefer welfare to liberal chauvinism, they typically implement the latter for health policies) and any factor of generosity comes from a social democratic coalition partner or not at all.